Impact of Social Media on Purchase Decisions: A Case Study of Pokhara Valley - Bhattarai, Bal Ram; Thapa, Sudan; Ranabhat, Deepesh; Sapkota, Pradeep; Ranabhat, Mala (Journal of Business and Management, 2023)
Background: In the modern digital landscape, the consumer purchase decision process has been transformed by the influence of social media. This evolution has also led to a paradigm shift in marketing strategies.Objectives: This research aimed to assess the impact of social media influencers on purchase decisions with special reference to Pokhara Valley.Methods: This study was conducted in the Pokhara Valley of Nepal, involving 250 respondents. The research utilized a quantitative approach with a descriptive research design. Primary data was collected through a self-administered survey questionnaire. Data analysis involved descriptive statistics and Partial Least Squares Structural Equation Modelling (PLS-SEM) to examine the impact of independent variables on the dependent variable. The study took place in 2023, spanning three months from January to April.Results: The results revealed that online communities have a positive and significant impact on purchase decisions (β = 0.202, p = 0.006). Similarly, perceived usefulness (β = 0.172, p = 0.019), ratings and reviews (β = 0.234, p = 0.002), and trust (β = 0.140, p = 0.035) significantly influence purchase decisions in a positive manner. However, recommendations and referrals do not have a significant impact on purchase decisions.Conclusion: This study concluded that individuals who actively participate in online communities, perceive social media as useful for product information and purchasing, rely on ratings and reviews, and place trust in the platform are more likely to make purchase decisions based on their online experiences. Understanding these factors and their implications can guide businesses and marketers in tailoring their strategies to effectively engage with consumers and drive purchasing behaviour.